PENGATURAN DAN PERAN BANK INDONESIA DALAM MEMPERKUAT SEKTOR PERBANKAN - Ninuk Triyanti (Perspektif, 2003)
Optimization of Indonesian Bank Role must be realized by means of Indonesian Bank independence as Central Bank. Thus, banking rate restructuring can be carried out significantly in order that economic crisis writing can be accomplished.